Factor XIII-A is involved in the regulation of gene expression in alternatively activated human macrophages - Töröcsik, Dániel; Széles, Lajos; Paragh, György, Jr.; Rákosy, Zsuzsa; Bárdos, Helga; Nagy, László; Balázs, Margit; Inbal, Aida; Ádány, Róza (Thrombosis and Haemostasis, 2010)
Factor XIII subunit A (FXIII-A) is one of the most overrepresented genes that is expressed during the alternative activation of macrophages. Based on its substrate profile and its cellular localisation, FXIII-A is thought to function as an intracellular/intranuclear transglutaminase. Our aim was to find role for the intracellular FXIII-A by comparing the microarray profiles of alternatively activated monocyte-derived macrophages. Microarray analyses of FXIII-A-deficient patients and healthy controls were evaluated, followed by functional clustering of the differentially expressed genes. After a 48-hour differentiation in the presence of interleukin 4 (IL4), 1,017 probes out of the 24,398 expressed in macrophages from FXIII-A- deficient samples were IL4 sensitive, while only 596 probes were IL4 sensitive in wild-type samples. Of these genes, 307 were induced in both the deficient and the wild-type macrophages. Our results revealed that FXIII-A has important role(s) in mediating gene expression changes in macrophages during alternative activation. Functional clustering of the target genes carried out using Cytoscape/BiNGO and Ingenuity Pathways Analysis programs showed that, in the absence of FXIII-A, the most prominent differences are related to immune functions and to wound response. Our findings suggest that functional impairment of macrophages at the level of gene expression regulation plays a role in the wound healing defects of FXIII-A-deficient patients.
Keywords: Factor XIII-A; macrophage; wound healing; interleukin 4